2013
DOI: 10.1160/th13-05-0400
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aspirin dose on adenosine diphosphate-mediated platelet activities

Abstract: Different aspirin dosing regimens have been suggested to impact outcomes when used in combination with adenosine diphosphate (ADP) P2Y12 receptor antagonists. Prior investigations have shown that not only aspirin, but also potent ADP P2Y12 receptor blockade can inhibit thromboxane A2-mediated platelet activation. The impact of aspirin dosing on ADP mediated platelet activities is unknown and represents the aim of this in vitro pilot pharmacodynamic (PD) investigation. Twenty-six patients with stable coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…The considered magnitude of aspirin benefit for patients with ACS and its very low cost has resulted in all other antiplatelet agents being tested on top of aspirin, with the assumption of additive effects of both medications. Nevertheless, in light of the central role of the P2Y12 signaling pathway on platelet activation and amplification processes, potent P2Y12 blockade can also lead to downregulation of other markers of platelet reactivity, including arachidonic acid-induced and collagen-induced aggregation …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The considered magnitude of aspirin benefit for patients with ACS and its very low cost has resulted in all other antiplatelet agents being tested on top of aspirin, with the assumption of additive effects of both medications. Nevertheless, in light of the central role of the P2Y12 signaling pathway on platelet activation and amplification processes, potent P2Y12 blockade can also lead to downregulation of other markers of platelet reactivity, including arachidonic acid-induced and collagen-induced aggregation …”
Section: Discussionmentioning
confidence: 99%
“…Yet aspirin still yields additive inhibition of arachidonic acid-induced and collagen-induced platelet aggregation, even in the presence of potent P2Y12 inhibition . Moreover, investigations have shown that high-dose aspirin does not interfere with the pharmacokinetic or pharmacodynamic effects of ticagrelor, and aspirin dosing does not modulate pharmacodynamic markers of P2Y12 signaling irrespective of the degree of P2Y12 receptor blockade . Therefore, the question remains as to whether the additive value of aspirin mediated through inhibition of TXA 2 -mediated platelet aggregation is offset by the inhibition of prostacyclin synthesis in vivo, which is generally not accurately assessed by laboratory studies .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clopidogrel has also been reported to enhance periodontal repair in rats through decreased inflammation [373]. P2Y 12 receptor antagonists are widely used in combination with aspirin for the treatment of thrombosis, especially for patients with acute coronary syndrome and those undergoing percutaneous coronary intervention [374,375]. Clopidogrel has also been reported to prevent endothelial dysfunction and vascular remodelling in aortas from hypertensive rats [376].…”
Section: Thrombosismentioning
confidence: 99%
“…Low cost and the benefit attributed to aspirin resulted in all other antiplatelet medications being tested on top of aspirin, with the assumption of additive and even synergistic effects of both agents. Nevertheless, in the context of the central role of the P2Y 12 signalling pathway on platelet activation and amplification processes, more potent P2Y 12 blockade was also shown to lead to downregulation of other markers of platelet reactivity, including arachidonic acid-and collagen-induced aggregation 2,20,21 . Aspirin was hypothesised to add little additional inhibition of platelet aggregation in the presence of potent P2Y 12 inhibitors 2,5,6 .…”
Section: Global Leaders Stopdapt-2 Smart-choice Twilightmentioning
confidence: 99%